KONTRIBUSI KONSEP DIRI TERHADAP PERENCANAAN ARAH KARIR SISWA (Studi pada Siswa Sekolah Menengah Atas Negeri 1 Padang Panjang) - NOFRITA S.Pdi, M.Pd, NOFRITA (Jurnal Pelangi : Research of Education and Development, 2011)
The 14-18 years old high school students begin to plan their future lineincluding secondary school plan. The secondary school has been a concern of highschool students and would be a big work that possibly determines their life andfuture. Many factors that contribute to students career direction plan, some ofthem are self-concept.The study is a quantitative one using the correlation analysis approach.Population including all students of XI grade in Padang Panjang Senior HighSchool 1 that amount 165. Sample used is 116 students that taken by proportionalrandom sampling technique considering the sex and field of study. The instrumentused to collect data is the questionnaires that having a tested validity andreliability. Data analysis is using correlation and regression technique throughSPSS program.The result of the study show that hypothesis above is significantly proved.The self-concept is contributing 16,9% towards students career direction plan. Theresults reveal that self-concept rate can not be ignored besides other variables thatalso considered to have same contribution. Therefore, it is hoped that thecounseling teachers are able to improve the counseling programs through a moreeffective and creative activities.